Brief visuospatial memory test-revised normative data and form equivalency for adults ages 80-89. Issue 6 (22nd July 2022) - Powell, Jessica; Blake, Lauren; Wyman-Chick, Kathryn; Daniel, Michael
Abstract: Objective: To provide normative data and examine form equivalency of the Brief Visuospatial Memory Test-Revised (BVMT-R) in a sample of 9 th decade adults. Method: The sample was comprised of 90 healthy individuals ages 80-84 (n = 42) and 85-89 (n = 48). The average years of education was 14.8 (2.4). The BVMT-R Forms 1 and 4 were administered in a counterbalanced order, one week apart. Form equivalency was conducted utilizing Analysis of Variance (ANOVA). Results: There were no significant gender, education, or MMSE differences between the two age groups or between the counterbalanced subgroups. There were no significant differences between Forms 1 and 4 for the 80-84 age group. However, BVMT-R Form 1 Trial 1 and Total Recall raw scores were significantly higher than those for Form 4 in the 85-89 age group. Conclusions: Individuals in their early 80s obtained comparable scores on Forms 1 and 4 of the BVMT-R; however, individuals in their late 80 s showed more difficulty learning and recalling information presented in Form 4 compared to Form 1. It is recommended that clinicians consider form-specific normative data with this population.